Weekly accumulative external load based on participation in football matches - Casamichana, D.; Agirrezabalaga, O.; Agirre, G.; Nakamura, F. Y.; Barba, E.; Martín-García, A.; Castellano, J. (International Journal of Sports Science & Coaching, 2024)
The aim of this study was to compare the weekly accumulative external load according to their participation in the previous match and the following match in three teams of different categories belonging to a football club. Sixty football players participated, belonging to the under-23 (U23, n: 20), U21 (n: 22) and U19 (n: 18) teams. Players were monitored by global positioning system devices during all training sessions and official matches. For the accumulative weekly load (from Monday to Sunday), the following external load variables were used: total distance covered (TD, m), distance covered at different speed thresholds (>14.0, >18.0, >21.0 and >24.0 km·h-1), the number of moderate-high intensity accelerations (ACC: >2 m·s-2, n) and decelerations (DEC: <-2 m·s-2, n), the player load (PL, arbitrary units, au) and the acceleration load (Aload, au). Players were grouped according to their participation in the previous and next matches: starter and starter (SS, when the player was a starter in both the previous and the following matches), starter and non-starter (SN), non-starter and starter (NS), and non-starter and non-starter (NN). This study revealed that NS and SS groups had a higher absolute and relative accumulative weekly load for the global indicators (Aload, PL and TD) in the three teams than NN and SN (range of ES: 0.1-3.4). This information would allow coaches to refine the required stimulation regarding players` role in the team based on the player's participation in the previous and next match.